Clinical Outcomes of Patients with Bleeding Peptic Ulcer; Tertiary Center Experience - Sardar, Anirudha; Islam, Md Shahidul; Dey, Palash Kumar; Dhali, Dipayan Kumer (Mediscope, 2024)
Background: Bleeding peptic ulcer remains an important cause of morbidity and mortality. Bleeding peptic ulcer (PUB) remains one of the most emergent and potentially fatal medical situations. However, the incidence of bleeding peptic ulcers not associated with H. pylori (Hp) infection or NSAID use varies considerably, and recent suggestions that patients with non-H. pylori–non-NSAID idiopathic bleeding peptic ulcers have a significantly higher mortality rate than patients with NSAID or H. pylori ulcers. Objective: The objective of this study was to demonstrate the epidemiological, clinical and endoscopic characteristics of peptic ulcer bleeding (PUB). Methods: This was a prospective study of patients who were admitted for peptic ulcers at Khulna Medical College Hospital Khulna, Bangladesh, from January 2021 to December 2021. Data were collected using a pretested and coded questionnaire and analyzed using SPSS computer software. Ethical approval to conduct the study was obtained from relevant authorities before the commencement of the study. Results: In this study, a total of 24 patients were included and analyzed. Regarding the age distribution of the study population, 11(45.83%) patients were <65 years of age, 9(37.50%) patients were from the age group 65-80 years and 4(16.67%) patients were aged >80 years. Also, 62.5 percent of patients were female and 37.5 percent were male. Among the study subjects, 14(58.33%) patients were treated by endoscopic therapy and 13(54.17%) patients had initial hemostasis. Initial hemostasis had some types also; 9(37.50%) patients had Epinephrine, 8(33.33%) patients had Epinephrine+endoclips, 5(20.83%) patients had endoclips. Conclusion: Three decades after the discovery of Hp, the etiologies of bleeding peptic ulcers are changing. However, diagnosis of Hp infection is still the priority in these patients. Invasive RUT is most frequently used, but this methodology is hampered by a high rate of false-negative results, especially in patients with UGI bleeding. Mediscope 2024;11(2): 77-81